1966
DOI: 10.1111/j.1365-2672.1966.tb03492.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microflora of Hand Washed Milk Bottles

Abstract: The examination of a series of 713 milk bottles cleansed by hand washing at producer-retailer farm dairies showed that though nearly 60% attained satisfactory bacteriological standards, about 30% gave high colony counts (> 600/bottle), while coli-esrogenes organisms were found i n 17% and milk spoilage organisms in 26% of them. The microflora of efficiently cleansed bottles, with colony counts of <200/bottle. waa dominated by micrococci and aerobic sporeforming rods. Only 3.7% of the 269 cultures from these bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1971
1971

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Hand washed milk bottles from producer-retailers rarely contain enough thermoduric bacteria to make a significant contribution to the heat resistant flora of milk placed in them. Griffiths, Morgan, Pritchard & Thomas (1952) and Thomas, King & Davies (1966) found that although about 50% of the bacteria isolated from farm bottles were therinoduric micrococci and sporeforming bacilli ; relatively few bottles (18%) contained more than one thermoduric organism per ml capacity.…”
Section: Incidence Of Thermoduric Bacteria In Producer-retailer Milk mentioning
confidence: 99%
“…Hand washed milk bottles from producer-retailers rarely contain enough thermoduric bacteria to make a significant contribution to the heat resistant flora of milk placed in them. Griffiths, Morgan, Pritchard & Thomas (1952) and Thomas, King & Davies (1966) found that although about 50% of the bacteria isolated from farm bottles were therinoduric micrococci and sporeforming bacilli ; relatively few bottles (18%) contained more than one thermoduric organism per ml capacity.…”
Section: Incidence Of Thermoduric Bacteria In Producer-retailer Milk mentioning
confidence: 99%